Exploitation of epigenetic variation of crop wild relatives for crop improvement and agrobiodiversity preservation - Varotto, Serena; Krugman, Tamar; Aiese Cigliano, Riccardo; Kashkush, Khalil; Kondić-Špika, Ankica; Aravanopoulos, Fillipos A; Pradillo, Monica; Consiglio, Federica; Aversano, Riccardo; Pecinka, Ales; Miladinović, Dragana (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2022)
Crop wild relatives (CWRs) are recognized as the best potential source of traits for crop improvement. However, successful crop improvement using CWR relies on identifying variation in genes controlling desired traits in plant germplasms and subsequently incorporating them into cultivars. Epigenetic diversity may provide an additional layer of variation within CWR and can contribute novel epialleles for key traits for crop improvement. There is emerging evidence that epigenetic variants of functional and/or agronomic importance exist in CWR gene pools. This provides a rationale for the conservation of epigenotypes of interest, thus contributing to agrobiodiversity preservation through conservation and (epi)genetic monitoring. Concepts and techniques of classical and modern breeding should consider integrating recent progress in epigenetics, initially by identifying their association with phenotypic variations and then by assessing their heritability and stability in subsequent generations. New tools available for epigenomic analysis offer the opportunity to capture epigenetic variation and integrate it into advanced (epi)breeding programmes. Advances in -omics have provided new insights into the sources and inheritance of epigenetic variation and enabled the efficient introduction of epi-traits from CWR into crops using epigenetic molecular markers, such as epiQTLs.
Keywords: epigenomika; Biodiversity; zemědělství; Epigenomics; biodiverzita; Agriculture